Impact of COVID-19 on Gastroenterology Fellowship Training - Shin, Hyun Phil; Cha, Jae Myung; Kim, Beom Kyung; Myung, Dae-Seong; Moon, Sung-Hoon; Song, Myeong Jun; Yoon, Seung Bae; Yoo, In Kyung; Lee, Jeong Hoon; Jun, Baek Gyu; Hyun, Jong Jin (The Korean journal of gastroenterology = Taehan Sohwagi Hakhoe chi, 2021)
The coronavirus disease 2019 (COVID-19) outbreak caused numerous social and cultural changes, but few studies focused on their effects on gastroenterology (GI) fellowship training. This study evaluated the impact of COVID-19 on GI fellowship training.Background/AimsThe coronavirus disease 2019 (COVID-19) outbreak caused numerous social and cultural changes, but few studies focused on their effects on gastroenterology (GI) fellowship training. This study evaluated the impact of COVID-19 on GI fellowship training.A web-based questionnaire was sent out to GI fellows in Korea between 15 February and 15 March 2021. The questionnaire included questions regarding the characteristics of GI fellows, perception of COVID-19 outbreak, impact of COVID-19 outbreak, and telemedicine on the education of a GI fellowship.MethodsA web-based questionnaire was sent out to GI fellows in Korea between 15 February and 15 March 2021. The questionnaire included questions regarding the characteristics of GI fellows, perception of COVID-19 outbreak, impact of COVID-19 outbreak, and telemedicine on the education of a GI fellowship.Among 111 answers, 94 respondents were analyzed. The GI fellows were provided with sufficient information about the COVID-19 outbreak (74.7%), well educated, and provided with personal protective equipment use (74.7% and 83.9%, respectively). On the other hand, outpatient schedule and volume decreased in 25.5% and 37.8% of respondents, respectively. Moreover, endoscopy sessions and volume decreased in 51.1% and 65.6% of respondents, respectively. As a result, 78.9% of respondents were concerned that the COVID-19 outbreak adversely affected their education. Telemedicine utilization was introduced during the COVID-19 outbreak, but only 20.0% and 10.6% of respondents agreed that telemedicine has benefits from the patient's and doctor's perspectives, respectively. In addition, only 25.9% of respondents were willing to continue telemedicine if adequately reimbursed, and 68.2% of respondents were concerned that it adversely affected their education.ResultsAmong 111 answers, 94 respondents were analyzed. The GI fellows were provided with sufficient information about the COVID-19 outbreak (74.7%), well educated, and provided with personal protective equipment use (74.7% and 83.9%, respectively). On the other hand, outpatient schedule and volume decreased in 25.5% and 37.8% of respondents, respectively. Moreover, endoscopy sessions and volume decreased in 51.1% and 65.6% of respondents, respectively. As a result, 78.9% of respondents were concerned that the COVID-19 outbreak adversely affected their education. Telemedicine utilization was introduced during the COVID-19 outbreak, but only 20.0% and 10.6% of respondents agreed that telemedicine has benefits from the patient's and doctor's perspectives, respectively. In addition, only 25.9% of respondents were willing to continue telemedicine if adequately reimbursed, and 68.2% of respondents were concerned that it adversely affected their education.The COVID-19 outbreak has adversely affected GI fellowship training in Korea for outpatient clinics, gastrointestinal endoscopy, educational conferences, and telemedicine. This study highlights that GI fellowship training needs more attention in the COVID-19 outbreak.ConclusionsThe COVID-19 outbreak has adversely affected GI fellowship training in Korea for outpatient clinics, gastrointestinal endoscopy, educational conferences, and telemedicine. This study highlights that GI fellowship training needs more attention in the COVID-19 outbreak.